Slow productivity the lost art of accomplishment without burnout - Newport, Cal 1982- (Portfolio/Penguin, 2024)
"The author of Digital Minimalism and Deep Work offers a philosophy for pursuing meaningful accomplishment while avoiding overload. History's most creative and impactful philosophers, scientists, artists, and writers mastered the art of producing valuable work with staying power. In this book, Cal Newport harnesses the wisdom of these traditional knowledge workers to transform modern jobs. Drawing from research on the habits and mindsets of a varied cast of thinkers from Galileo and Isaac Newton to Jane Austen and Georgia O'Keefe, Newport lays out the key principles of "slow productivity" and provides step-by-step advice for workers to replace the standard notion of productivity with a slower, more humane alternative."